EXPLORING THE CONSISTENCY OF HIGHER ORDER RISK PREFERENCES. (11th January 2020) - Haering, Alexander; Heinrich, Timo; Mayrhofer, Thomas
Abstract: This study measures higher order risk preferences and their consistency. We explore the role of country differences, the variation of stakes, and the framing of lotteries. We observe a robust dichotomous pattern of choice behavior in China, the United States, and Germany. The majority of choices are consistent with mixed risk aversion or mixed risk‐loving behavior. We also find this pattern after a 10‐fold increase in the stakes. Finally, our results reveal that this pattern is strengthened if the lotteries are displayed in compound instead of reduced form. In a follow‐up study, we explore potential explanations for this framing effect.